Responsabilidade Social Corporativa: o caso da Samarco S/A em Anchieta, ES - Herkner, Elisa Marly Heringer (2022)
This work aims to study the activities classified as Corporate Social Responsibility of the company Samarco Mineração S/A, a joint venture owned by Companhia Vale do Rio Doce and BHP Billiton Ltda. The company extracts itabirite ore in the municipalities of Mariana and Ouro Preto, in Minas Gerais, transports it through pipelines to Anchieta, located on the coast of Espírito Santo, WHERE, through pelletizing plants, it processes the ore into pellets in order to export to the foreign market. The choice of the object of study is justified by the Fundão tailings dam failure in Mariana, on 11/15/2015, which put an end to the company’s upward trajectory of expansion, success and high profitability. Considered the biggest mining dam disaster in the world, it caused multiple environmental and socioeconomic damages in the municipality of Mariana and in the entire Doce River. The question that guided the research aimed to understand what strategies were used by the company, especially with respect to the communities directly impacted, to obtain their consent, trust and belief that the company`s business is beneficial and prosperous for them. The theoretical and methodological basis that guided the process and the research findings was based on the theoretical-methodological model of the Global Network of Mineral Production (GNMP) and in the literature review on Corporate Social Responsibility. The combination of the categories of these two theoretical contributions provided elements to think about CSR practices in the case of the mining company Samarco S/A. Based on the understanding provided by these contributions, a critical analysis of the Annual Sustainability Reports of Samarco, from 2005 to 2015, was carried out. Through Nvivo Software, a qualitative content research was performed to identify CSR actions. The evaluation showed that most actions were directed to sustainable environmental development and social development, considering the socioeconomic, historical and cultural context of the company. The analysis showed that communication actions, compliance with terms of commitment (TAC), education and socio-environmental protection activities, infrastructure improvement works, strengthening of leadership and encouraging entrepreneurship predominated in the period. In light of the literature, we conclude that the company invests in CSR to create lasting social bonds, mechanisms of dependence, improvement of its image and reputation, in order to minimize criticism and neutralize possible Corporate Social Risks.